2019
DOI: 10.18632/aging.102313
|View full text |Cite
|
Sign up to set email alerts
|

SNHG22 overexpression indicates poor prognosis and induces chemotherapy resistance via the miR-2467/Gal-1 signaling pathway in epithelial ovarian carcinoma

Abstract: Recently, an increasing number of studies have reported that dysregulation of long noncoding RNAs (lncRNAs) plays an important role in cancer initiation and progression, including in epithelial ovarian carcinoma (EOC). However, little is known about the detailed biological functions of the lncRNA small nucleolar RNA host gene 22 (SNHG22) during the progression of EOC. Here, we found that SNHG22 was significantly increased in EOC tissues and was significantly associated with a low level of differentiation. Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…In our work, SNHG22 was utilized to be our research object. In accordance with previous research, SNHG22 was proved to be highly expressed and could induce chemotherapy resistance through miR-2467/Gal-1 axis in epithelial ovarian carcinoma [13]. In our research, we detected abnormally strong expression of SNHG22 in TNBC tissues and cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our work, SNHG22 was utilized to be our research object. In accordance with previous research, SNHG22 was proved to be highly expressed and could induce chemotherapy resistance through miR-2467/Gal-1 axis in epithelial ovarian carcinoma [13]. In our research, we detected abnormally strong expression of SNHG22 in TNBC tissues and cells.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, PVT1 was reported to facilitate malignant phenotypes of pancreatic cancer cells via absorbing miR-448 [12]. Small nucleolar RNA host gene 22 (SNHG22) is a novel lncRNA which was discovered as highly expressed and as a tumor-promoter in epithelial ovarian carcinoma cells through the miR-2467/ Gal-1 axis [13]. Nevertheless, the regulatory mechanism and function of SNHG22 in TNBC have not been elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 LncRNA has been shown to exert various biological functions through diverse mechanisms, such as epigenetic regulation and microRNA sponging. 9,10 Increasing reports indicate that lncRNA regulates the development and progression of human cancers. [11][12][13] LncRNAs may regulate proliferation, invasiveness and differentiation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…20 Some researchers have reported the upregulated expression of SNHG22 in EOC, PTC, and ccRCC, and whose expression indicated poor prognosis in the three types of human malignancies. [11][12][13] In this study, we rst explored the expression patterns of SNHG22 in ANT, CRA, and CRC tissues, and found that SNHG22 expression was gradually upregulated in ANTs, CRA, and TTs. The high expression level of SNHG22 was associated with advanced T stage, node involvement, metastasis, and poor survival in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several reports have found that SNHG22 contributed to cell growth, migration, invasion, and chemotherapy resistance in epithelial ovarian carcinoma (EOC), papillary thyroid cancer (PTC) and clear cell renal cell carcinoma (ccRCC). [11][12][13] Besides, upregulated SNHG22 was shown in TTs as compared with that in the ANTs, and whose high expression indicated poor prognosis in the three types of human malignancies. [11][12][13] To our knowledge, the biological role and expression patterns of SNHG22 have not been examined in human CRC.…”
Section: Introductionmentioning
confidence: 96%